IDEOLOGICAL WORK OF PARTY BODIES IN THE FIRST PERIOD OF THE GREAT PATRIOTIC WAR (1941-1942) - Gadzieva, Z N (History, Archeology and Ethnography of the Caucasus, 2015)
The article covers the main directions of the ideological and political work in Dagestan at the beginning of the Great Patriotic War. The author notes that the wide agitation conducted by the party and soviet bodies among the people of Dagestan was aimed at the fight against the fascist invaders. The article deals with the value of propaganda and agitation function of the press during the first years of the war.
Keywords: Dagestan; agitation; meeting; propaganda; sanitary brigade; defence committee; people’s militia